2021
DOI: 10.1038/s41598-020-80292-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term surgical outcomes of primary retropupillary iris claw intraocular lens implantation for the treatment of intraocular lens dislocation

Abstract: We aimed to investigate the efficacy and safety of primary retropupillary iris claw intraocular lens (R-IOL) implantation in patients with complete intraocular lens (IOL) dislocation. In this single-center retrospective case series, we reviewed the medical records of patients who underwent R-IOL implantation surgery with pars plana vitrectomy for the treatment of IOL dislocation between September 2014 and July 2019. The primary outcome was change in visual acuity (VA) up to 24 months postoperatively. The secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 48 publications
(65 reference statements)
2
21
2
2
Order By: Relevance
“…Increased postoperative astigmatism after IOL exchange has always been a critical hurdle for good postoperative vision. 6 , 11–13 Kristianslund et al reported that the mean SIA magnitude was 1.12 ± 0.85 D at 6 months after a 5.5-mm scleral pocket arcuate incision and retropupillary iris-claw IOL implantation, which was significantly higher than the SIA of the IOL reposition. 13 Choi et al also reported a significant increase in corneal astigmatism after a 5.5-mm sclerocorneal incision and retropupillary iris-claw IOL implantation; although, no information regarding SIA was included in the data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased postoperative astigmatism after IOL exchange has always been a critical hurdle for good postoperative vision. 6 , 11–13 Kristianslund et al reported that the mean SIA magnitude was 1.12 ± 0.85 D at 6 months after a 5.5-mm scleral pocket arcuate incision and retropupillary iris-claw IOL implantation, which was significantly higher than the SIA of the IOL reposition. 13 Choi et al also reported a significant increase in corneal astigmatism after a 5.5-mm sclerocorneal incision and retropupillary iris-claw IOL implantation; although, no information regarding SIA was included in the data.…”
Section: Discussionmentioning
confidence: 99%
“… 6–11 However, because the IOL is rigid, its implantation requires a large sclerocorneal incision, which often results in high surgically induced astigmatism (SIA). 9 , 11–13 …”
Section: Introductionmentioning
confidence: 99%
“… 32 Choi et al showed that the ECL was not significant after 1 month postoperatively, signifying that the ECL was mainly due to factors related to surgery rather than the problem of ICIOL itself. 27 Forlini et al observed no significant ECL after 5 years of follow-up. 36 …”
Section: Postoperative Outcomesmentioning
confidence: 95%
“… 68 Studies on retropupillary ICIOL have shown a considerable variation in ECL ranging from 3%-43%. 14–16 , 23 , 25 , 27 , 28 , 30–33 , 36 , 42–44 , 46 , 47 , 49–51 , 56 Dalby et al, in a prospective comparative clinical trial, observed no significant difference in ECL following ICIOL implantation (15%) and IOL repositioning (18%) for late in-the-bag IOL dislocation at the end of 2 years. 64 In contrast, Kristianslund et al reported a significant postoperative ECL of 10% in the ICIOL group and a non-significant postoperative ECL of 3% in the repositioning group.…”
Section: Postoperative Outcomesmentioning
confidence: 98%
See 1 more Smart Citation